Antioxidant Activity and Phytochemical Screening of Ethanol Extract from Ruellia napifera Leaves - Efendi, Meilisa Rusdiana Surya; Anisa, Zuffa; Setyaningrum, Dyah; Trisnawati, Ade (Jurnal Pijar Mipa, 2025)
Exploration of the chemical profile and antioxidant properties of ethanol extract derived from Ruellia napifera leaves is very important, considering the usefulness of these leaves for use in natural therapy products. This research investigates the identification of secondary metabolite compounds and the antioxidant activity of ethanol extract from Ruellia napifera leaves. The objectives are to determine the types of secondary metabolite compounds present and to evaluate the antioxidant potential using the DPPH (1,1-diphenyl-2-picrylhydrazyl) radical scavenging method. Ethanol extracts were prepared using the maceration method at durations of 24 hours. Phytochemical tests revealed the presence of flavonoids, alkaloids, saponins, and steroids. Antioxidant activity was measured through IC50 values, indicating the extract’s ability to inhibit 50% of the DPPH radicals. The IC50 values obtained were 10.66 μg/mL. For comparison, vitamin C as a positive control exhibited an IC50 of 2.49 μg/mL. These results suggest that the Gempur Batu leaf extract has strong antioxidant potential. These findings suggest that this extract from Ruellia napifera leaves holds potential for developing natural antioxidant-based therapeutic products or herbal medicine formulations.